Combating Overtourism: The Use of Web-GIS in Visualizing Tourist Distribution and Travel Patterns - Cholid Fauzi; Syifaa Novianti; Chandra Budhi Septyandi (Journal of Tourism Sustainability, 2022)
Web-GIS in the tourism sector can be done using website technology, namely by visualization based on tourism spatial attributes that display polygon-based patterns and points of tourist attraction locations to combat overtourism in tourist attractions. With the development of geospatial technology, tourists' distribution and travel patterns can be visualized by collecting data on tourist visits to tourist attractions and their routes. With the YWDM method, this web-gis was developed using the YWDM methodology with several phases according to the methods used. This application uses an open-source programming language, namely Javascript, and uses JSON as an upstream geodatabase. The results show that Web-GIS visualization of the distribution and travel patterns can make it easier to monitor the density of a tourist attraction. It is well developed in providing more accurate information on the distribution and density of tourist attractions. With the YWDM methodology, visualization can be done like the software development stage and equipped with steps in need for spatial data management.